Envenenamento de cavalos por Equisetum spp. (cavalinha) - de T Alvim, Paulo (Revista Ceres, 1948)
The author reports cases of poisoning of horses by Equisetum, which seems to occur very frequently in the region known as “Triângulo Mineiro” (western Minas Gerais State). He gives a literature review on the toxic principles of Equisetum, symptoms of poisoning, and treatments.